Kualitas Produk Ditinjau Dari Persepsi Konsumen Pentol Kluwung: Si Pentol Sehat Pelangi - Nurul Fitria; Leonard Adrie Manafe; Wahyuni Cholifa Sari (Universitas Hamzanwadi, 2021)
The culinary business has an important role in the country's economy due to minimized unemployment and reduce poverty. Pentol Kluwung business is presented to fulfill the consumer’s wishes to consume healthy and safe meatball. As is known, many meatballs sold in the market whose no safety healthy. Inside Pentol Kluwung, consisting many nutritional content. Namely beef protein, flour carbohydrates and fiber, vitamins and minerals obtained from natural dyes derived from dragon fruit, spinach and turmeric. Free from harmful chemicals such as formalin and borax. Along the way, the researcher realized that products quality needed to be improved by looking at the consumer's perception. This study aims to determine the product quality in terms of consumer perceptions. Qualitative research methods used in this study, the surrounding environmental phenomena can be examined directly, data collected through dissemination and interviews after data analysis and conclusion drawing. Purposive sampling used in this research. The results showed that the order of the first factors that determine the quality of Pentol Kluwung products is the taste of the product, the second is price and the third is promotion. Whatsapp application is consumers' first choice regarding easy-to-reach promotional media